Twelve kinds of ice - Obed, Ellen Bryan, 1944- (Houghton Mifflin Books for Children, 2012)
From the first ice, a thin skin on a bucket of water, through thickly-iced fields, streams, and gardens, a girl, her family, and friends anticipate and enjoy a winter of skating, ending with an ice show complete with costumes, refreshments, and clowns.